What are the risks of contact sport during pregnancy: a survey-based investigation - Jones, P. A. T.; Brockwell, E.; Dufour, S.; Hassan, A.; Matenchuk, B. A.; Davenport, M. H. (Sports Medicine, 2025)
Background: Current guidelines recommend avoiding activities with the risk of contact during pregnancy, despite a lack of empirical data to support this recommendation. As a result, individuals who participate in contact and collision sports such as football or rugby are often confronted with difficult decisions and, in the absence of clear guidance, may resort to making choices based on personal experience, limited advice, or fear. Objective: We aimed to examine the impact of continued participation in contact sport during pregnancy on maternal and fetal health outcomes. Methods: We conducted an online survey study of individuals (= 18 years of age) who participated in contact or collision sports during pregnancy. The survey collected self-reported information on participant demographics, sport participation (type, hours, and contact exposure) from pre-conception to postpartum, maternal and infant health outcomes, feelings towards continuing/stopping participation in sport, and medical advice received during the perinatal period. Odds ratios or relative risk ratios with 95% confidence intervals were calculated for all categorical outcomes using regression adjusted for relevant covariates to compare outcomes in individuals who stopped participating in contact sport = 12 weeks and > 12 weeks gestation as well as individuals who did and did not sustain a hit (contact) during pregnancy. Results: Between September 2023 and February 2024, 395 participants (age 34.6 ± 5.0, months postpartum 27.2 ± 34.3; primarily from Australia, Canada, the UK, and the USA) were recruited to participate in the survey. Participants participated in contact sports for an average of 12.8 ± 6.4 weeks of pregnancy with 84 individuals sustaining hard hits and 114 individuals sustaining cumulative low impact contact. Participants reported partaking in a total of 11,687.2 h of contact exposure during pregnancy and the rate of adverse events was 1.11 per 1000 h of exposure. Overall, continued participation in contact sport during pregnancy was associated with better mental health status. Over half of participants stated that they had concerns about participating in contact sports during their pregnancy; however, 90% felt "happy" or "very happy" about continuing their sport during pregnancy. Conclusions: Pregnant individuals continue to participate in contact sports during pregnancy. Participants who continued participating in contact sports were more likely to report decreased depression. Continued participation in contact activities was not associated with the odds of other maternal or fetal complications during pregnancy or the postpartum period. Further investigation is required to direct safe participation in contact sports during pregnancy.